Tumor Necrosis Factor α Blockade: An Opportunity to Tackle Breast Cancer - Mercogliano, María Florencia; Bruni, Sofía; Elizalde, Patricia V.; Schillaci, Roxana (Frontiers in Oncology, 2020)
Breast cancer is the most commonly diagnosed cancer and the leading cause of mortality by malignancy in women and represents a main problem for public health worldwide. Tumor necrosis factor α (TNFα) is a pro-inflammatory cytokine whose expression is increased in a variety of cancers. In particular, in breast cancer it correlates with augmented tumor cell proliferation, higher malignancy grade, increased occurrence of metastasis and general poor prognosis for the patient. These characteristics highlight TNFα as an attractive therapeutic target, and consequently, the study of soluble and transmembrane TNFα effects and its receptors in breast cancer is an area of active research. In this review we summarize the recent findings on TNFα participation in luminal, HER2-positive and triple negative breast cancer progression and metastasis. Also, we describe TNFα role on immune response against tumors and on chemotherapy, hormone therapy, HER2-targeted therapy and anti-immune checkpoint therapy resistance in breast cancer. Furthermore, we discuss the use of TNFα blocking strategies as potential therapies and their clinical relevance for breast cancer. These TNFα blocking agents have long been used in the clinical setting to treat inflammatory and autoimmune diseases. TNFα blockade can be achieved by monoclonal antibodies (such as infliximab, adalimumab, etc.), fusion proteins (etanercept) and dominant negative proteins (INB03). Here we address the different effects of each compound and also analyze the use of potential biomarkers in the selection of patients who would benefit from a combination of TNFα blocking agents with HER2-targeted treatments to prevent or overcome therapy resistance in breast cancer.